Associations between the atrial electromechanical interval, atrial remodelling and outcome of catheter ablation in paroxysmal atrial fibrillation. Issue 3 (13th December 2010) - Chao, Tze-Fan; Sung, Shih-Hsien; Wang, Kang-Ling; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Tuan, Ta-Chuan; Suenari, Kazuyoshi; Li, Cheng-Hung; Ueng, Kuo-Chang; Wu, Tsu-Juey; et al.
Abstract : Objective: The atrial electromechanical (PA–PDI) interval was reported to be a useful predictor of new-onset atrial fibrillation (AF) and the occurrence of AF after coronary artery bypass surgery. The aim of this study was to investigate the associations of the electromechanical interval with atrial substrate properties and the outcome of catheter ablation in paroxysmal AF patients. Methods: 132 paroxysmal AF patients who had received catheter ablation were enrolled. The electromechanical interval was determined as the time interval from the initiation of P-wave deflection to the peak of the mitral inflow A-wave on pulse-wave Doppler imaging. The left atrial voltage and total activation time were collected before pulmonary vein isolation. Every patient underwent standard follow-up after catheter ablation. Results: The PA–PDI interval was significantly correlated with the left atrial dimension (r=0.419, p=0.003), left atrial volume (r=0.827, p<0.001), left atrial voltage (r=−0.451, p<0.001) and left atrial activation time (r=0.547, p<0.001). During a follow-up of 23±13 months, 36 patients (27% of the study population) had AF recurrence. The PA–PDI interval and left atrial volume were independent predictors of AF recurrence. At a cut-point of 160 ms, the Kaplan–Meier survival analysis showed that a long PA–PDI interval significantly predicted AF recurrence. Conclusions: The PA–PDI interval can reflect the process of left atrial remodelling, such as a left atrial enlargement, prolonged activation time and decreased voltage. It was a convenient parameter for predicting recurrence after catheter ablation of paroxysmal AF.